2020
DOI: 10.25046/aj050144
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning as a Tool of Enhancing of Entrepreneurial Attitude of Students

Abstract: The increase in employment and productivity is crucial for the economic growth of the European Union. Specifically, the employment of young people needs to be increased. The excessively theoretical approach to education is identified as one of the most significant problems in the educational system. Acquirement of practical experience while study, presents for the students the advantage when applying for a job or starting their own business. Self-employment or entrepreneurship might be one of the partial solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…(2021) revealed that Project-Based Learning on the independence of students' interest in entrepreneurship has a significant influence of 38.2% contribution. Research from Paľová et al. (2020) revealed that implementing project-based learning and virtual laboratories supports entrepreneurship education in the two study programs offered by the economics faculty.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) revealed that Project-Based Learning on the independence of students' interest in entrepreneurship has a significant influence of 38.2% contribution. Research from Paľová et al. (2020) revealed that implementing project-based learning and virtual laboratories supports entrepreneurship education in the two study programs offered by the economics faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Bandera et al (2018) found that experiential entrepreneurship education supported by technology has a positive influence on students' inclination to take risks. Similarly, research conducted by Pal'Ová et al (2020) indicates that project-based learning supported by technology enhances students' motivation and engagement in the learning process. Furthermore, in a case study conducted by Oliver & Oliver (2022), experiential learning activities were found to enhance the understanding of one's role and responsibilities in a business simulation.…”
Section: ) Entrepreneurship Education In Today's Challengesmentioning
confidence: 97%
“…Several gathered studies indicate that experiential learning and project-based learning are considered effective in entrepreneurship education. (Bandera et al, 2018;Oliver & Oliver, 2022;Pal'Ová et al, 2020). Bandera et al (2018) found that experiential entrepreneurship education supported by technology has a positive influence on students' inclination to take risks.…”
Section: ) Entrepreneurship Education In Today's Challengesmentioning
confidence: 99%
See 2 more Smart Citations